Effect of Using Thermophilic Bacteria as Start Inoculum on Microbial Aspect of Pulp and Paper Mill Sludge Composting Process - Ngo Thi Tuong Chau (Science Faculty of Chiang Mai University, 2019)
Pulp and paper mill sludge (PPMS) is poorly colonized with thermophilic bacteria. However, evidence to support the need for inoculation to facilitate PPMS composting has only been demonstrated in one instance. The objective of this study was to investigate the effect of thermophilic bacteria used as a start inoculum on the microbial populations, enzyme activities, bacterial communities and species succession in the PPMS composting process using the plate counting method or most probable number method, API ZYM kit and spectrophotometric methods, denaturing gradient gel electrophoresis (DGGE) of 16S rDNA amplicons and dominant sequencing analyses, respectively. The results showed that the number of microbial populations and activities of extracellular enzyme were almost higher in the inoculated compost than in the non-inoculated compost. Simultaneously, there was the high positive correlation between the number of nitrogen-fixing bacteria and phosphatase activity. Besides, the DGGE profiles and statistical analyses demonstrated that the inoculation with thermophilic bacteria improved the bacterial community structure and diversity of compost. Species of genus Luteimonas, Sorangium, Alpha proteobacterium and Povalibacter were dominant in the inoculated compost at the certain stages of the composting process. It was recommended to use thermophilic bacteria as a start inoculum to improve the PPMS composting process.